RESIKO DISALAH GUNAKAN SERTIFIKAT HAK MILIK TANAH YANG TIDAK DIBALIK NAMA DAN UPAYA HUKUM YANG DITEMPUH - anggusti, martono; Roida Nababan; Mokosoina Ntuacademy (Magister Hukum Universitas HKBP Nommensen, 2022)
In this day and age, many people are in dire need there is land. Many people also use this land as a future investment front. Because land prices rise every year. This one investmentIt is also closely related to buying and selling land. Definition of buying and selling land according to customary law is an act of transfer of rights, which is cash, real and bright. The nature of cash means Cash, is the transfer of rights by the sellertogether with payment by the buyer and immediately the rights are availableswitch. One of the legal acts of transferring ownership rights to land is bybuying and selling land. In the current practice of buying and selling land, this is expectedthere is legal certainty that can guarantee the continuation of these activitiesthrough the reverse of the name of the land title certificate. Reverse the name of the land title certificate What is done by buying and selling is a legal act of transferring rights other things, except that transfer of rights through auction can only be registered if proven by a deed made by the authorized PPAT. Objective The expected writing in this research is: To analyze the process of changing the name of a title certificate when buying and selling land; To analyze legal consequences if you do not change your name in the buying and selling process land, to analyze the legal measures that can be taken against the perpetrators use of land certificates. This research uses normative research methods, with a focus on collecting data as primary, secondary or tertiary data. Technique Data collection includes data analysis, which ensures proper interpretation of the data systematic, clear, and accurate to provide meaningful insights. Results This research is the Implementation of Transfer of Names of Ownership Certificates in Buying and Selling Land carried out by the Deli Serdang Land Office against the certificate Land ownership rights are legally impaired due to ownership certificates previously had been involved in buying and selling with other people. Apart from that, come back the name on the title certificate is not known to the person has civil rights to the land. For the community there must also be more find out about name change procedures, which are in accordance with regulations applicable laws. To avoid a possible problem happen. Apart from that, increasing awareness in carrying out buying and selling transactionsIn accordance with applicable regulations, this is the application of PP No. 24 years old 1997 Concerning Land Registration